Literature Review: Kejadian Resistensi Pada Penggunaan Antibiotik - Cindy Ivana Putri; M.Fitra Wardhana; Femmy Andrifianie; Muhammad Iqbal (Medula, 2023)
Antibiotic resistance is the ability of microorganisms to inhibit the action of antimicrobial agents and this phenomenon occurs when antibiotics lose their efficiency to inhibit bacterial growth. The increasing use of antibiotics in various health and agricultural sectors has led to the emergence of antibiotic resistance worldwide. Its irrational use can cause several problems. This incident causes antibiotic therapy to be no longer efficient and increases the cost of therapy. This resistance occurs in several types of microorganisms with a high prevalence that threatens human health. Antibiotic resistance can arise from mutations in pre-existing bacterial genomes. Mutations due to the external environment make a smaller contribution to the occurrence of resistance. Therefore, this literature review aims to provide an overview of the incidence of resistance in the use of antibiotics. The literature search was carried out using the Pubmed, Google Scholar and Mendeley electronic databases. The inclusion criteria in writing this literature review are articles in Indonesian and English with a range of article publications in the last 10 years (2013-2022). Research articles that cannot be accessed completely will be excluded. Overall the studies found and analyzed reported the incidence of resistance to the use of antibiotics. Almost all studies describe the percentage of occurrence of antibiotic resistance against certain bacteria. The increasing use of antibiotics has created high evolutionary pressure for the emergence of antibiotic resistance for bacterial survival.